How Do Patients’ Preferences Compare to the Present Spectrum of Diabetes Research? - Arnolds, S.; Heckermann, S.; Koch, C.; Heissmann, N.; Sawicki, P. T. (Experimental and Clinical Endocrinology & Diabetes, 2013)
To compare patients’ preferences in diabetes research to the current scientific research spectrum as presented during annual meetings of the European Association for the Study of Diabetes (EASD).After dividing all scientific activities in diabetes research into 9 main fields, a questionnaire was published in a popular German weekly news magazine, inviting diabetic patients to express their research preferences. Thereafter, all abstracts accepted for publication at 2 recent EASD meetings were allocated to one of these research fields.In May and July 2011 the questionnaire was answered by 652 patients with diabetes, 205 relatives and 61 other persons interested. The most important research fields were “development, pathophysiology and prevention of diabetes” (25.6%), “transplantation and cell therapy” (19.4%) and “blood glucose measurement and artificial pancreas” (16.5%). The most often covered topic of the 2 645 EASD abstracts was “development, pathophysiology and prevention” (46.3%), followed by “diabetes complications in man” (17.5%) and “special situations, training, psychology, treatment- and care structures” (10.5%).Views of diabetic patients and their relatives regarding their preferred research fields may differ when compared to current scientific activity in diabetology. Diabetic patients and their relatives should be involved in the weighting and selection of research topics more often.
Keywords: diabetes; fields of research; patient preferences; consumer views